DSpace statistics API - Orth, Alan S. (International Livestock Research Institute, 2018)
DSpace stores item view and download events in a Solr "statistics" core. This information is available for use in the various DSpace user interfaces, but is not exposed externally via any APIs. The DSpace 4+ REST API, for example, only exposes information about communities, collections, item metadata, and bitstreams.